2009
DOI: 10.1107/s0108270109043728
|View full text |Cite
|
Sign up to set email alerts
|

Two regioisomers of condensed thioheterocyclic triazine synthesized from 6-phenyl-3-thioxo-2,3,4,5-tetrahydro-1,2,4-triazin-5-one

Abstract: In the crystal structure of 6-phenyl-3-thioxo-2,3,4,5-tetrahydro-1,2,4-triazin-5-one, C(9)H(7)N(3)OS, (I), the 1,2,4-triazine moieties are connected by face-to-face contacts through two kinds of double hydrogen bonds (N-H...O and N-H...S), which form planar ribbons along the a axis. The ribbons are crosslinked through C-H...pi interactions between the phenyl rings. The molecular structures of two regioisomeric compounds, namely 6-phenyl-2,3-dihydro-7H-1,3-thiazolo[3,2-b][1,2,4]triazin-7-one, C(11)H(9)N(3)OS, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The ferromagnetic interaction of 5a also decreased with the color change. Generally, the vapochromism is mainly induced due to two reasons: (i) a coordination exchange reaction between the metal and the solvents [15][16][17][18] and (ii) a change in the crystal packing due to inclusion of solvents. [19][20][21][22][23][24][25] In this case, we suggest that a dynamic disproportionation reaction of 5a (CuCl 2 /3a = 1:1) occurred and produced a new aggregation state composed of the mononuclear complex 6a (CuCl 2 /3a = 1:2) and the solvated metal ion in the solid.…”
Section: Magnetic Properties and Vapochromismmentioning
confidence: 99%
See 1 more Smart Citation
“…The ferromagnetic interaction of 5a also decreased with the color change. Generally, the vapochromism is mainly induced due to two reasons: (i) a coordination exchange reaction between the metal and the solvents [15][16][17][18] and (ii) a change in the crystal packing due to inclusion of solvents. [19][20][21][22][23][24][25] In this case, we suggest that a dynamic disproportionation reaction of 5a (CuCl 2 /3a = 1:1) occurred and produced a new aggregation state composed of the mononuclear complex 6a (CuCl 2 /3a = 1:2) and the solvated metal ion in the solid.…”
Section: Magnetic Properties and Vapochromismmentioning
confidence: 99%
“…[16] The ethyl-(2b and 3b) and benzyl-substituted (2c and 3c) Scheme 1. Synthetic routes for the condensed heterocyclic rings and their complexation reactions, (x) dibromoethane, EtONa, (y) CuCl 2 ·2H 2 O, 2-propanol, (z) 2-propanol and/or water.…”
Section: Introductionmentioning
confidence: 99%
“…19 entries showed R 2 2 (8) motifs characterized by two N-HÁ Á ÁO hydrogen bonds; the S atoms take part as acceptors only in five of them [refcodes LACJIJ (Tashkhodzhaev et al, 2002), XUHJIY (Pawlowski et al, 2009), XEXWAZ, XEXWED and XEXWIH (Balalaie et al, 2006)], whereby chains stabilized by N-HÁ Á ÁS hydrogen bonds are observed only in XUHJIY. Nine structures contain two different R 2 2 (8) patterns with either two N-HÁ Á ÁO or two N-HÁ Á ÁS hydrogen bonds [refcodes CASPUI (Hu et al, 2005), CUKBOA (Hori et al, 2009), GEMCAC (Read et al, 1988), PABPAL (Chierotti et al, 2010), RAPNAY (Long et al, 2005), TURCIL01 (Tiekink, 1989), TURCIL02 (Munshi & Guru Row, 2006), WIVJAM (Coxall et al, 2000) and ZEWDOU (Ferrari et al, 1995)]. Furthermore, six entries showed R 2 2 (8) interactions consisting of two N-HÁ Á ÁS hydrogen bonds [refcodes FALWOF (Orzeszko et al, 2004), JESWEK (Xue et al, 2006), MTURAC (Hawkinson, 1975), PABNIR (Chierotti et al, 2010), VOKBUT (Luo et al, 2008) and ZUWMUZ (Branch et al, 1996)].…”
Section: Figurementioning
confidence: 99%
“…Qualitative and quantitative structural characteristics of heterocyclic compounds are significant in studying reaction mechanisms as well as in the synthesis of novel biologically active materials [ 1 - 4 ]. It is well known that the majority of saturated six-membered heterocycles adopt the chair conformation whereas the structure of aromatic derivatives is almost planar [ 5 - 9 ]. Deviations from the planarity may arise due to a set of various steric and electronic factors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%